Dictionary of shipping terms French-English and English-French = Dictionnaire du transport maritime : français-anglais et anglais-français - Brodie, Peter R. 1947- (Informa Law from Routledge, 2018)
Updated and expanded, this new edition of Peter Brodie's dictionary provides a reference tool for all of those who use or operate cargo ships, bothtramp and liner, or who are concerned with their use.